The Experiment of Experience: Ronald Sukenick and Mark Amerika's Performative Theory of Writing. (October 2016) - Esposito, Lucia
Abstract : The paper analyses some texts by the American author Ronald Sukenick (particularly the 1969 short story 'The Death of the Novel', included in a collection by the same name) and links them to some recent works by Mark Amerika in order to show the way experimental writing can be conveniently used as a means to investigate the nature and role of literature in critical transition periods. Sukenick started to write in the sixties, at a time in which a prevailing feeling of the novel's exhaustion dominated, and experimented a new kind of non-mimetic, experiential writing – literature performed as an extemporaneous event and an embodied experience – that Amerika was to foreground later, in the period in which literature was being ferried to the digital world. The two authors (and both professors), who also collaborated on some projects, seem to share the same penchant for an acrobatic (con)fusion of storytelling and theoretical and critical analysis, and the result is a textual performance that situates the metacommentary as literary production.